2020
DOI: 10.1111/ppc.12421
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic stress disorders and depression among male inpatient adults involved in the Lebanese war

Abstract: Purpose: to evaluate factors associated with posttraumatic stress disorder (PTSD) and depression in a sample of hospitalized Lebanese adult males who directly or indirectly were involved in armed conflicts.Design: Cross-sectional.Methods: Seventy-seven hospitalized males were enrolled between June and December 2016. The Hamilton Anxiety and Depression Scale and the Mini International Neuropsychiatric Interview were used to assess anxiety, depression, and PTSD.Results: Participation in war (adjusted odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Mental Health Care in the US troops is seen with utmost importance, integrating mental care into their daily work life via centralized workload management; consolidation of professionally trained mental health domains under integrated behavioral health departments such as psychiatry, clinical psychology, psychiatric nursing, and social work services; creation of satellite mental health clinics embedded within brigade work areas; extension of psychosocial help to also the soldier's family members to name a few (42). From our analyses, the US army reports much lower prevalence of psychiatric symptoms (7.10-33.3%) (43,44), compared to their Israelian counterparts (39.6-47.8%) (45,46), suggesting that integration of mental health resources is beneficial to the mental wellness of a population (47). While not explored in this paper, we recommend that further research can be done to investigate if there is the presence of non-report bias, or other stigma associated with reduced report of mental health symptoms to improve the detection and outreach of at-risk individuals in the military.…”
Section: Discussionmentioning
confidence: 76%
“…Mental Health Care in the US troops is seen with utmost importance, integrating mental care into their daily work life via centralized workload management; consolidation of professionally trained mental health domains under integrated behavioral health departments such as psychiatry, clinical psychology, psychiatric nursing, and social work services; creation of satellite mental health clinics embedded within brigade work areas; extension of psychosocial help to also the soldier's family members to name a few (42). From our analyses, the US army reports much lower prevalence of psychiatric symptoms (7.10-33.3%) (43,44), compared to their Israelian counterparts (39.6-47.8%) (45,46), suggesting that integration of mental health resources is beneficial to the mental wellness of a population (47). While not explored in this paper, we recommend that further research can be done to investigate if there is the presence of non-report bias, or other stigma associated with reduced report of mental health symptoms to improve the detection and outreach of at-risk individuals in the military.…”
Section: Discussionmentioning
confidence: 76%
“…The antecedents, measurements, incidence rates, causes, and effects of COVID-19 information overload on mental health are widely studied (2,6,9,10,22); however, in addition to negative emotions and psychological illness, chain effects need to be considered. Therefore, according to previous studies that indicated a relationship between COVID-19 information overload and anxiety, depression, and PTSD symptoms (9,10,49,50), we investigated the relationships among these variables. We found that COVID-19 information overload has a small direct effect on the development of PTSD symptoms; moreover, (2,10).…”
Section: Disscussionmentioning
confidence: 99%
“…According to Yaacoub's study, the relationship between depression and PTSD can be explained by feelings of insecurity, which lead to a more distorted memory of the event and to more intense emotions and hurt. This aggravation of an already distressing trauma increases the chances of developing PTSD (49). Therefore, COVID-19 information overload might affect individuals' PTSD symptoms through the psychological pathways mentioned above.…”
Section: Disscussionmentioning
confidence: 99%
“…For instance, a study by Farhood et al showed that 97.7% of a studied cohort of civilians from the South of Lebanon witnessed, experienced, or heard of a traumatic war-related event, resulting in a PTSD prevalence of 29.3% (L. Farhood et al, 2006). A more recent study by Yaacoub and colleagues evaluated depression and PTSD factors in 77 hospitalized adult Lebanese males who were directly or indirectly involved in a war or armed conflict (Yaacoub et al, 2020). Using the Hamilton Anxiety and Depression scales as well as the Mini-International Neuropsychiatric Interview, the authors demonstrated that participation in the war was linked to higher PTSD rates.…”
Section: Discussionmentioning
confidence: 99%